Residents of Late Nineteenth-Century Port Districts: A Comparative Dataset from Antwerp and Boston, 1880–1900 - Kristof Loockx (Journal of Open Humanities Data)
This data paper presents a historical dataset that provides a comparative snapshot of the social composition of two transatlantic port districts during a period of significant urban and maritime transformation. It documents over 5,000 individuals residing in the main commercial thoroughfares of Antwerp and Boston in 1880 and 1900. The data was extracted from Belgian population registers and U.S. census records and systematically entered into a structured database to allow for comparative analysis. Hosted on Zenodo, the dataset provides scholars with opportunities for reuse in research on maritime communities, demography, urban history, labour migration and broader patterns of social change during the period of late industrialization.